Development and Evaluation of Sasak Local Wisdom-Based Instructional Materials Integrated with the Science, Environment, Technology, and Society (SETS) Learning Model to Enhance Elementary School Students' Critical and Creative Reasoning Skills - Hesty Febrian Widyana; Sukardi Sukardi; Moh. Irawan Zain (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
Critical and creative reasoning skills are essential twenty-first-century competencies that elementary school students need to develop. However, evidence from the Trends in International Mathematics and Science Study (TIMSS) and preliminary field studies indicates that Indonesian elementary students continue to demonstrate relatively low levels of these competencies. This study aimed to develop and evaluate the validity, practicality, and effectiveness of Sasak local wisdom-based instructional materials integrated with the Science, Environment, Technology, and Society (SETS) learning model to enhance elementary school students' critical and creative reasoning skills. This research employed a Research and Development (R&D) approach using the Four-D (4D) model, consisting of the Define, Design, Develop, and Disseminate stages. The study involved elementary school students from Cluster 03, Jonggat District, Central Lombok Regency. The effectiveness of the developed instructional materials was examined using a quasi-experimental design with experimental and control groups. The product developed was a Grade IV Phase B science instructional material entitled “Lingkunganku Bersih Desaku Lestari”, integrating the SETS learning process with visual elements reflecting Sasak local culture. Expert validation indicated that the instructional materials were highly feasible in terms of content, language, media design, and assessment instruments. Teacher and student responses also demonstrated that the materials were highly practical for classroom implementation. Furthermore, the instructional materials significantly improved students' critical and creative reasoning skills, as indicated by independent- and paired-samples t-tests (p < .001). The N-gain analysis showed high improvement in critical reasoning (0.72) and moderate improvement in creative reasoning (0.57) in the experimental group, while the control group demonstrated low improvement. These findings demonstrate that integrating Sasak local wisdom into the SETS learning model provides an effective contextual learning approach for improving elementary school students' critical and creative reasoning skills.